Efeitos indiretos da tolerância oral a zeína melhoram a cicatrização de pele em camundongos diabéticos - Thiago Cantaruti Anselmo (2016)
At the beginning of the twentieth century it was observed that animals that had been fed with animal chow that contained corn proteins did not react immunologically to zein. Today we know that the absorption of intact or partially digested proteins through intestinal mucosa is a common occurrence after meals. These proteins interfere with the activity of the immune system and a common result of these interferences is oral tolerance. The first reports on the influence of dietary proteins on the immune activity were made with plant and animal proteins but most studies on oral tolerance have been made using animal-derived proteins. Animal proteins, such as ovalbumin (OVA) is not a regular diet component of mice and, for oral tolerance induction, it has to be introduced in their drinking water. Mice that drink a solution containing OVA before immunization with OVA+Al(OH)3 form less antibodies than those animals that do not receive OVA. However the ingestion of OVA does not interfere with immunization to other proteins, except when during the immunization with the second protein the tolerated protein is also given, a phenomenon named "indirect effects of oral tolerance". Indirect effects of oral tolerance to OVA also inhibit inflammatory reactions, such as those triggered by carrageenan and improves skin wound healing in mice. In here we show that, the indirect effects of oral tolerance triggered by intraperitoneal injection of zein minutes before a skin wound in both health and diabetic mice reduce the inflammatory infiltrate and improve the healing of cutaneous wound. Mice that have received i.p. injection of zein+Al(OH)3 before cutaneuos wound had reduced scar. Moreover, we show that indirect effects of oral tolerance can improve the healing of a lesion already in process or in conditions where the healing process is more difficult to occur as in diabeties. The indirect effects of oral tolerance triggered by i.p. injection of zein increased the level of TGF-β3 in the wound bed. These results indicate that parenteral injection of tolerated proteins may be explored as a possibility to treat skin ulcers in cases where cutaneous wound healing is more difficult to occur.